ANALISIS EFEKTIVITAS KEPEMIMPINAN VIRTUAL KEPALA SEKOLAH DALAM MENINGKATKAN MOTIVASI KERJA GURU SEKOLAH MENENGAH ATAS - Eka Diana; Hiflatus Sunnah; Sri Wahyuni Khoiriyah (Muróbbî: Jurnal Ilmu Pendidikan, 2021)
This study aims to analyze the effectiveness of the principal's virtual leadership in relation to increasing teacher work motivation in the new normal era and the factors that influence it. This type of research uses a mix of qualitative and quantitative. The research location is in SMA Nurul Jadid Paiton Probolinggo. The research sample amounted to 20 people chosen randomly from the entire research population. Data collection techniques used interviews, documentation studies and questionnaires. The data analysis technique used descriptive statistics with the t-test of one sample based on the sample used less than 30. The results of the t-test obtained an average value of 82.7% which was in the effective category. The supporting factors for virtual leadership consist of communication skills and social networking skills. The inhibiting factors consist of geographical conditions and building trust.